Eksistensi Sistem Pendidikan Pesantren Terpadu Pada Era Modernisasi di Pesantren Dar Faqih Qurani Aceh Timur - Muhammad, Taufiq; Fitriani, Fitriani; Suhelayanti; NurAsma (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
The existence of the Islamic boarding school education system in the modernization era is an effort and ability carried out by an Islamic boarding school to defend itself from the modernization era, in which many demands and needs of society have grown and developed. So Islamic boarding schools now have to adapt not only to the development of Islamic education but also to develop students in the world of education and non-education. At the Dar Faqih Qur'ani Islamic Boarding School which has been operating since 2021, this research tries to determine the efforts made by the Islamic boarding school to maintain the existence of an integrated Islamic boarding school education system in the era of modernization. To collect data in this research, qualitative descriptive methods were used, including observation, documentation and interviews. This research uses inductive data analysis techniques, namely analyzing data with a management model from specific to general, from which conclusions can be drawn about events that occurred at the research location. The results of this research explain that in the era of modernization, the Dar Faqih Qur'ani Islamic Boarding School in East Aceh in 2023 will have an integrated education system, namely, first: the Islamic boarding school education system at the Dar Faqih Integrated Islamic Boarding School in East Aceh, and second: the efforts made by the Dar Faqih Integrated Islamic Boarding School. Faqih in maintaining its existence in the Modernization Era.